Twenty New Records of Bees (Hymenoptera, Apoidea) for Sardinia (Italy) - Vittorio Nobile; Roberto Catania; Pietro Niolu; Michelina Pusceddu; Alberto Satta; Ignazio Floris; Simone Flaminio; Salvatore Bella; Marino Quaranta (Insects, 2021)
In Sardinia, the second largest Mediterranean island, 316 species of bees are known. Here, for the first time, the following 20 taxa are reported: Colletes cunicularius (Linnaeus, 1761), and C. eous Morice, 1904 (Colletidae); Andrena humilis Imhoff, 1832, A. granulosa Pérez, 1902, A. cineraria (Linnaeus, 1758), A. pallitarsis Pérez, 1903, A. rugulosa Stöckhert, 1935, A. savignyi Spinola, 1838, and A. tenuistriata Pérez, 1895 (Andrenidae); Sphecodes reticulatus Thomson, 1870 (Halictidae); Lithurgus tibialis Morawitz, 1875, Chelostoma emarginatum (Nylander, 1856), Dioxys cinctus (Jurine, 1807), Coelioxys caudatus Spinola, 1838, C. obtusus Pérez, 1884, and Megachile ericetorum (Lepeletier, 1841) (Megachilidae); and Nomada melathoracica Imhoff, 1834, N. pulchra Arnold, 1888, Eucera proxima Morawitz, 1875 and Tetralonia malvae (Rossi, 1790) (Apidae). N. pulchra is reported for the first time in Italy.